1990
DOI: 10.1116/1.576754
|View full text |Cite
|
Sign up to set email alerts
|

Surface studies of polyether–polyester copolymers and blends

Abstract: The surface composition and morphology of a series of thermoplastic elastomers based on polyester (PBT)–polyether (PPG) copolymers have been studied using x-ray photospectroscopy (XPS) and static secondary-ion-mass spectroscopy (SIMS). In all cases, an enrichment of the polyether soft block at the surface is observed. The degree of preferential surface adsorption is greater for molded specimens compared ot the solvent cast films. The enrichment factor (surface content/bulk content) is greater for speciment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…A fast precipitation condition resulted in a uniform but superficial calcification pattern at the surface of Polyactive. This phenomenon could be related to the observations of Burrell et al, 38 who showed that the surface area of segmented polyester polyether block copolymers are enriched in flexible segment as opposed to the bulk. During a slow coating New crack forms and propagates both in the coating and in the interface when the stress exceeds a specific value.…”
Section: Discussionsupporting
confidence: 64%
“…A fast precipitation condition resulted in a uniform but superficial calcification pattern at the surface of Polyactive. This phenomenon could be related to the observations of Burrell et al, 38 who showed that the surface area of segmented polyester polyether block copolymers are enriched in flexible segment as opposed to the bulk. During a slow coating New crack forms and propagates both in the coating and in the interface when the stress exceeds a specific value.…”
Section: Discussionsupporting
confidence: 64%
“…A typical example is the successive linking of hard polyester segments to soft polyether chains, allowing to tailor the mechanic properties of the resulting elastomer as well as its surface properties for a subsequent coating step or interaction at the polymer/air interface. Speci®cally, Burrell et al (1990) studied the surface composition of a poly(butylene terephtalate)-PPG segmented block copolymer in moulded and solvent cast specimens. Using the peak intensity ratio of the signals at m/z 59 R H over m/z 149 (C 8 H 4 O 3 ), it was found that the moulding led to a substantial higher concentration of the soft PPG segments at the surface.…”
Section: Surface Segregation Of Block Polymersmentioning
confidence: 99%
“…PBT-based TPEE has been developed, such as poly(butylene terephthalate- co -polyethylene glycol) (PBT- co -PEG) [ 16 , 31 ] and poly(butylene terephthalate- co -polypropylene glycol) (PBT- co -PPG) [ 32 ], revealing varied characteristics depending on different compositions. Poly(butylene terephthalate- co -tetramethylene ether glycol) (PBT- co -PTMEG) copolymer was first commercialized under the trademark “Hytrel” (Du pont, Wilmington, DE, United States) as engineering plastics in 1972 [ 33 , 34 , 35 ], and the morphology [ 17 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], properties [ 45 , 46 , 47 , 48 , 49 ], interactions between hard segments and soft segments [ 50 , 51 ], and structure of the crystalline [ 36 , 38 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] and amorphous phase [ 5 , 17 , 49 , 59 ] have been studied extensively.…”
Section: Introductionmentioning
confidence: 99%